Does The Implementation Of SA 600 Cause Shifting Of Audit Clients And Reducing Audit Quality? Evidence From Indonesia - Fitriany Fitriany; Andi Darmawan; Arie Wibowo; Syahril Ali; Sugeng Praptoyo (Jurnal Reviu Akuntansi dan Keuangan, 2020)
This research was conducted to investigate the impact of implementation of SA 600 on shifting of audit clients and reducing of audit quality in Indonesia. SA 600 was issued in 2013 in order to mitigate the problem of audit failure in group entities where the group auditor is responsible for the entire audit process, particularly the audit quality in component entities or subsidiaries. In its implementation, SA 600 has received several complaints related to audit quality and shifting of audit clients. The research method is using primary data from questionnaires that was distributed to auditors and focus group discussions with auditors and users. The respondents of this research are 367 auditors of which 63% were audit partners. This research found that SA 600 can improve audit quality when its implementation is carried out according to audit standards. However, the implementation of SA 600 has an impact on the shifting of component or subsidiary company clients which move to the group or parent company auditors.